The association between suicidal ideation and sleep quality in elderly individuals: A cross-sectional study in Shandong, China. (October 2017) - Qian, Yangyang; Sun, Long; Zhou, Chengchao; Ge, Dandan; Zhang, Li
Abstract: Previous studies have identified global associations between sleep quality and suicidal ideation. However, little is known regarding the relationship between sleep quality and suicidal ideation among Chinese older adults. We examined the relationship between sleep quality and suicidal ideation in older adults in China. A cross-sectional study was conducted in 3313 seniors in Shandong, China. Suicidal ideation was assessed using the interviewees' answers to the question "Have you ever seriously considered wanting to die?". Sleep quality was assessed using the Pittsburgh Sleep Quality Index. Logistic regression was performed to estimate odds ratios and 95% confidence intervals adjusted for confounders. When controlling for sex, age, living condition, economic status, marital status, education, past occupation, relationship with children, non-communicable diseases, and mental health, the odds of suicidal ideation increased in association with an increase in the total score for sleep quality and its components (subjective sleep quality, sleep duration, habitual sleep efficiency, and daytime dysfunction). Poor sleep quality was associated with increased odds of suicidal ideation in Chinese older adults. Sleep-based interventions should be developed to prevent suicide in older adults in China. Highlights: A large sample of 3313 participants based on a community survey provided a real profile of suicidal ideation. This is one of only a few studies of suicidal ideation in Chinese seniors. When controlling for other variables, the odds of suicidal ideation increased in association with an increase in the sleep quality score. More attention should be paid to seniors who have sleep disorders. Sleep-based interventions should be developed to prevent suicide in elderly individuals in China.